Pengembangan Sensor Kloramfenikol Berbasis Imobilisasi Bovine Serum Albumin (BSA) pada Selulosa Asetat dengan Metode Spektroflorometri (The Development of Chloramphenicol Sensor Based on Bovine Serum Albumin (BSA) Immobilization on Cellulose Acetate using Spectrofluorometry Method) - Dhany Alghifari; Bambang Kuswandi; Dwi Koko Pratoko (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
The chloramphenicol usage in shrimp cultivation is an example of antibiotics abuse that have adverse effects for health. According to Indonesian Drug and Food Agency (BPOM) survey, it showed that from 14 samples of shrimp test, entirely contain residues of chloramphenicol. In this context, the sensor has been developed base on cellulose acetate membrane immobilized with bovine serum albumin (BSA). The chloramphenicol sensor has a linearity range of 2-12 μg/ml and the r value of -0.997. The value of limit of detection is 0.157 μg/ml and limit of quantification is 0.472 μg/ml. The RSD value of repeatability is 1.542 % and the value of intermediate precision is 1.058%. The average value of recovery as the parameter an accuracy test of 95.338 ± 0.636% and this sensor has a good selectivity tests to erythromycin, pellets and shrimp meat. The result also shown in good agreement with the conventional spectrofluorometry method Keywords: shrimp, chloramphenicol, BSA, sensor, spectrofluorometry